Evaluating acceptability of the Inpatient Mental Health Pharmaceutical Assessment and Care Tool (IMPACT): A multi-site study in the United Kingdom - Fatima Q. Alshaikhmubarak; Richard N. Keers; Petra Brown; Penny J. Lewis (PLoS ONE, 2026)
Background The Inpatient Mental Health Pharmaceutical Assessment and Care Tool (IMPACT) was developed to assist pharmacy teams in identifying high risk patients for early intervention. Evaluation of the IMPACT tool is important to ensure its feasibility and effectiveness. This study reports the first evaluation of the IMPACT tool aiming to explore its acceptability by mental health inpatient pharmacy teams using an iterative qualitative approach. Methods Between October 2024 and February 2025, pharmacy staff from five National Health Service (NHS) organisations retrospectively applied the IMPACT tool on patients that they had provided pharmaceutical care to, completed a reflection sheet, and attended an online focus group. Training was delivered to participants before initiating the study and the Theoretical Framework of Acceptability guided the content and analysis of the focus groups. Results Four focus groups and one dual interview were conducted with 12 pharmacists and 5 pharmacy technicians. The tool was viewed as self-explanatory and effective. Most participants were confident using the tool, though some pharmacy technicians reported difficulties due to clinical criteria (e.g., blood tests interpretation) that was not part of their usual duties. Following the first focus group, some changes were made such as clarifying or combining some risk-indicators. These changes were well-received by subsequent participants and recommendations and insights gained from all participants assisted in improving the tool. Conclusion This study revealed that the IMPACT tool was acceptable by pharmacy team members and resulted in a refined version. Future work should further explore the tool’s feasibility and impact using mixed methods approaches.